А х+1х+2-х+3х+4=0б 10х^2-2x-35x-1=31в x-2x-3-x+1x-4=0г 12x^2-4x-33x+1=-2Решите уравнение

1 Январь 0001



а) (х+1)(х+2)-(х+3)(х+4)=0
б) 10х^2-(2x-3)(5x-1)=31
в) (x-2)(x-3)-(x+1)(x-4)=0
г) 12x^2-(4x-3)(3x+1)=-2
Решите уравнение

  • а)(х+1)(х+2)-(х+3)(х+4)=0

    х в квадрате+х+2х+2-(х в квадрате+3х+4х+12)

    х в квадрате+х+2х+2-х в квадрате-3х-4х-12=0

    -4х-10=0

    -4х=10

    х=-2.5

    б)10х в квадрате-(2х-3)(5х-1)=31

    10х в квадрате-(10х в квадрате-15х-2х+3)=31

    10х в квадрате-10х в квадрате+15х+2х-3-31=0



    17х-34=0

    17х=34

    х=2

    в)(х-2)(х-3)-(х+1)(х-4)=0

    х в квадрате-2х-3х+6-(х в квадрате+х-4х-4)=0

    х в квадрате-2х-3х+6-х в квадрате-х+4х+4=0

    -6х+4х+10=0

    -2х+10=0

    -2х=-10/:(-)2

    х=5

    г)12х в квадрате-(4х-3)(3х+1)=-2

    12х в квадрате-(12х-9х+4х-3)=-2

    12х в квадрате-12х+9х-4х+3=-2

    5х+3=-2

    5х+3+2=0

    5х+5=0

    5х=-5/:5

    х=-1

  • а)

    X2+2X+X+2=X2+4X-3X-12=0

    4X-10=0

    4X=10

    X=0,25

     









Алгебра

Комментарии закрыты.